DINAMIKA KEMISKINAN IMPLEMENTASI QGIS DALAM MENGIDENTIFIKASI PERUBAHAN DI JAWA TENGAH TAHUN 2021-2023 - Eni Imro’atun Wahyu Septiani; Bambang Agus Herlambang, Ahmad Khoirul Anam (ADMIN: Jurnal Administrasi Negara, 2024)
Poverty is the most basic problem that is the government's main concern. The causes of poverty are very diverse in various regions. This research aims to analyze the influence of unemployment rates, years of schooling and life expectancy on poverty in districts/cities in Central Java Province. The data used in this research is secondary data for 2021-2023. The method used is the analytical method used in this research is descriptive analysis using tables and graphs to become the best regression model. The research results show that the unemployment rate variable has a positive influence on the poverty rate. Meanwhile, the average length of schooling and life expectancy have a negative effect on poverty levels in districts/cities in Central Java Province. By using QGIS, it is hoped that more accurate patterns and distribution of poverty can be found which can become a basis for local governments in formulating more effective and sustainable poverty alleviation policies and programs in Central Java. The results of this research will become policy recommendations to make the region better, poverty reduced and society prosperous